2011
DOI: 10.3892/or.2011.1576
|View full text |Cite
|
Sign up to set email alerts
|

Association of aberrant DNA methylation with clinicopathological features in breast cancer

Abstract: Abstract. Aberrant DNA methylation is responsible for the epigenetic silencing of genes associated with tumourigenesis and progression of cancer. In this study, we assessed the methylation status of eight genes in 49 snap-frozen primary breast tumours. Epigenetic alterations of 8 genes were analysed with methylation-specific polymerase chain reaction (MS-PCR) (DCR1, DAPK1, RASSF1A and DCR2) or methylationsensitive high-resolution melting analysis (MS-HRM) (APC, MGMT, GSTP1 and PTEN). MS-HRM performance was val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
3
35
3
Order By: Relevance
“…Several previous reports of the literature suggest that MGMT hypermethylation results in gene silencing and increased rate of mutations in normal colonic mucosa that might represent an initiating step in the development of mismatch repair-deficient CRC. [22][23][24][25] We also observed an age-related increase in MGMT methylation in CRC tissues in agreement with previous reports by Tserga et al 26 that showed a correlation between age and MGMT promoter methylation in breast cancer specimens, and Menigatti et al 21 that showed an age related increase of MGMT methylation in healthy colonic mucosa samples. CDKN2A was methylated in 29% of CRC samples and both RASSF1A and hMLH1 in 16.8% of them; by contrast, they resulted methylated only in a few healthy mucosa tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Several previous reports of the literature suggest that MGMT hypermethylation results in gene silencing and increased rate of mutations in normal colonic mucosa that might represent an initiating step in the development of mismatch repair-deficient CRC. [22][23][24][25] We also observed an age-related increase in MGMT methylation in CRC tissues in agreement with previous reports by Tserga et al 26 that showed a correlation between age and MGMT promoter methylation in breast cancer specimens, and Menigatti et al 21 that showed an age related increase of MGMT methylation in healthy colonic mucosa samples. CDKN2A was methylated in 29% of CRC samples and both RASSF1A and hMLH1 in 16.8% of them; by contrast, they resulted methylated only in a few healthy mucosa tissues.…”
Section: Discussionsupporting
confidence: 92%
“…MGMT methylation correlates with the loss of MGMT expression that leads cells transform to cancer cells. MGMT methylation had been found in 22% breast cancer patients [6]. In our case, no MGMT expression was detected in specimens from TNBC tumor, which suggests that DNA methylation may be involved in the specific gene profile of the rare phenotype of the patient.…”
Section: Discussioncontrasting
confidence: 46%
“…Barekati et al [5] recently studied methylation signature of lymph node metastases of breast cancer and found the heterogeneity of DNA methylation between primary tumor and metastatic lesion. The [6] O-methylguanine-DNA methyltransferase (MGMT) is enzyme play important role in DNA repair. MGMT methylation correlates with the loss of MGMT expression that leads cells transform to cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, O6-methylguanine has the tendency to pair with thymine during replication [22] and trigger the conversion of G-to-A during base-pairing, causing mutations together with other factors. The MGMT protein restores guanine and inactivates itself during the process [4], providing to the cell a significant defence mechanism against tumourigenesis [23]. MGMT methylation has been reported to occur in one-third of all breast cancers, irrespective of the hormone receptors and Her-2 status [24].…”
Section: Introductionmentioning
confidence: 99%